Biogeochemical responses to water management: Insights from the regulated Geum River, Korea - Min-Young Lee; Tae-Hoon Kim; Yongwon Kim; Hyebin Kim; Tae-Woo Kang; Sung-Eun Park (Journal of Hydrology: Regional Studies, 2025)
Study region: The Geum River estuary, located on the western coast of South Korea. Study focus: This study examines how contrasting water management regimes (gate-closing vs. opening) influence biogeochemical processes in this regulated estuary. We compared conditions during August 2021 (gate-closing) and August 2022 (gate-opening), periods with starkly different residence times (3.5 vs. 0.5 days) that resulted in distinct biogeochemical dynamics. By analyzing organic matter composition, nutrient speciation, and isotopic signatures, we aimed to elucidate the specific mechanisms driving these transformations under different hydrological conditions. New hydrological insights for the region: Gate operations act as a biogeochemical switch, fundamentally altering the estuary’s function between transport and processing. During gate-opening, the short 0.5-day residence time created a transport-dominated, P-limited system that rapidly exported terrestrial organic matter with minimal biological processing. This maintained a NO3⁻-dominated nitrogen pool (ODIN/TDIN ratio ∼0.29). Conversely, gate-closing extended the residence time to 3.5 days, transforming the estuary into a processing-dominated system. This longer duration promoted enhanced biological activity, evidenced by a 2.8-fold increase in bottom-water chlorophyll-a. This internal productivity drove a significant shift in nitrogen speciation from oxidized to reduced forms, with RDIN/TDIN ratios increasing to ∼0.76, marking a clear temporal transition from P to N limitation. Dual nitrate isotopic analyses (δ15N-NO3⁻ and δ18O-NO3⁻) confirmed these distinct nitrogen cycling patterns, demonstrating that management decisions directly dictate the estuarine ecosystem's state and function.